GNSS land subsidence observations along the northern coastline of Java, Indonesia - Susilo Susilo; Rino Salman; Wawan Hermawan; Risna Widyaningrum; Sidik Tri Wibowo; Yustisi Ardhitasari Lumban-Gaol; Irwan Meilano; Sang-Ho Yun (Scientific Data, 2023)
Abstract Land subsidence in cities along the northern coastline of Java has been at a worrying level. Monitoring efforts using geodetic data reveal that Jakarta, Pekalongan, Semarang, and Demak subside at least ~9x faster than the present-day rate of global sea level rise, which affects the cities’ future urban viability. In this study, we publish a time series of the precise 3D displacements observed by twenty continuous Global Navigation Satellite System (GNSS) stations between 2010 and 2021. These are the first open-to-the-public and rigorously processed GNSS datasets that are useful for accurately quantifying land subsidence in the densely populated sinking cities in Java. The data also provides a way to tie other geodetic observations, such as Interferometric Synthetic Aperture Radar (InSAR), to a global reference frame in an attempt to build worldwide observations of coastal land subsidence.